Characterization of Briquette from sugarcane (Saccharum officinarum) bagasse with jackfruit (Artocarpus heterophyllus) seed starch as binder. - Espera, Leza Andrea A.
In this study, production and characterization of briquettes from sugarcane bagasse using Jackfruit seed starch as binder was carried out. The Jackfruit seeds were manually cleaned, sun-dried, and ground. The sugarcane bagasse was carbonized then mixed with the binder using three different concentrations: 30 percent, 35 percent and 40 percent per weight of bagasse. The briquettes were then air-dried. Ash, moisture, volatile matter, fixed carbon content and heating value determination were conducted to characterize the briquette. Test results showed that ash content varied from 6.33 percent to 8.87 percent, moisture content varied from 0.51 percent to 1.44 percent, volatile matter varied from 3.54 percent to 3.89 percent, fixed carbon content varied from 87.08 percent to 88.29 percent and heating value varied from a value of 10,700 BTU/lb to 11,594 BTU/lb. It was also found out that the mixing ratio had a significant effect on the physico-chemical properties and heating value of the briquettes. Increasing concentration of the binder increased the moisture and volatile matter while decreasing ash content and heating value. Among the three concentrations, the 30 percent binder per weight bagasse was the most efficient. Results were also compared with that of a commercially available briquette and briquettes made from bagasse were proven to be more efficient. It could be concluded that production of sugarcane bagasse briquettes using jackfruit seed as binder is feasible, cheaper, and environmentally friendly and that it can compete favourably with commercially available briquettes.